2015
DOI: 10.1007/s13404-015-0171-3
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for visual detection of glutathione S-transferase activity and inhibition using cysteamine-capped gold nanoparticles as colorimetric probes

Abstract: An operationally simple colorimetric method for measuring glutathione S-transferase (GST) activity was developed using cysteamine-capped gold nanoparticles (AuNPs) in this work. This method was based that GST can catalyze the reaction of 1-chloro-2,4-dinitrobenzene (CDNB) and glutathione (GSH) to produce a conjugate (CDNB-SG). GSH could induce the aggregation of AuNPs, whereas the conjugate could not induce the aggregation of AuNPs. Thus, GST activity can be facilely assayed with the naked eye or a simple colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…This indicates a possible interaction of CDNB with the GSH coating of QDs, which is prevented in the presence of GST. This further points out that if CDNB‐GSH conjugate (CDNB‐SG) is formed, that does not cause particle precipitation or detrimental drop in the luminescence of the particles (Ren, Zhou, Xu, & Li, ).…”
Section: Resultsmentioning
confidence: 91%
“…This indicates a possible interaction of CDNB with the GSH coating of QDs, which is prevented in the presence of GST. This further points out that if CDNB‐GSH conjugate (CDNB‐SG) is formed, that does not cause particle precipitation or detrimental drop in the luminescence of the particles (Ren, Zhou, Xu, & Li, ).…”
Section: Resultsmentioning
confidence: 91%
“…Phytochemicals of soybean, including saponins and isoflavones, are considered good sources of anticancer activity (Yoon et al 2005). Recent studies revealed GST-pi enzymes are frequently over expressed in neoplastic tissues and have been considered as important markers of a number of tumors, such as lung, ovarian, breast, and gastric carcinoma (Ren et al 2015). Thus, a component that inhibits GSTpi enzyme activity could be considered to possess good anticancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested by ultrasonic treatment, and the GSTP enzymatic activity was determined by using glutathione S -transferase (GSH-ST) kit (Nanjing Jiancheng Bioengineering Institute, Nanjing, China). The reactions were terminated, and the enzyme kinetics of the conjugation of 1-chloro-2,4-dinitrobenzene to GSH was determined as previously described ( 43 ).…”
Section: Methodsmentioning
confidence: 99%